Magnetic response and critical current properties of mesoscopic-size YBCO superconducting samples - Lisboa Filho, Paulo Noronha [UNESP]; Deimling, C. V.; Ortiz, W. A. (Iop Publishing Ltd, 2010)
In this contribution superconducting specimens of YBa(2)Cu(3)O(7-delta) were synthesized by a modified polymeric precursor method, yielding a ceramic powder with particles of mesoscopic-size. Samples of this powder were then pressed into pellets and sintered under different conditions. The critical current density was analyzed by isothermal AC-susceptibility measurements as a function of the excitation field, as well as with isothermal DC-magnetization runs at different values of the applied field. Relevant features of the magnetic response could be associated to the microstructure of the specimens and, in particular, to the superconducting intra- and intergranular critical current properties.